Antifungal Activity of Essential Oils Against Candida Species Isolated from Clinical Samples - Córdoba, Susana Beatriz (2019)
We evaluated the in vitro antifungal activity of essential oils obtained from the aromatic plants Laurus nobilis, Thymus vulgaris, Mentha piperita, Cymbopogon citratus and Lippia junelliana against the following Candida species isolated from clinical samples: C. krusei (n = 10); C. albicans (n = 50); C. glabrata (n = 70) and C. parapsilosis (n = 80). The minimal inhibitory concentration (MIC) was determined according to EDef 7.3.1 document from EUCAST. Amphotericin B and fluconazole were the antifungal drugs used as inhibition control. The concentration ranges evaluated were 0.4–800 and 0.03–128 mg l⁻¹ for essential oils and antifungal drugs, respectively. MIC₅₀ and MIC₉₀, mode and ranges were calculated. All the Candida spp. evaluated were susceptible to amphotericin B (MIC ≤ 1 mg l⁻¹), while fluconazole was inactive for C. krusei (MIC ≥ 32 mg l⁻¹) and intermediate for C. glabrata (MIC ≤ 32 mg l⁻¹). The essential oils showed antifungal activity on Candida spp. tested with MIC₉₀ values ranging from 0.8 to 800 mg l⁻¹. In general, the most active essential oils were L. nobilis and T. vulgaris (MIC₉₀ 0.8–0.16 mg l⁻¹), and the least active was C. officinalis (MIC₉₀ 400–800 mg l⁻¹). C. krusei was inhibited by 5/6 of the essential oils evaluated, and C. glabrata was the least susceptible one. This in vitro study confirms the antifungal activity of these six essential oils assayed which could be a potential source of new molecules useful to control fungal infections caused by some Candida species, including those resistant to antifungal drugs.